A case of nonarteritic ischemic optic neuropathy (NAION) in a male patient taking sildenafil - Boshier, A; Pambakian, N; Shakir, S A W (International journal of clinical pharmacology and therapeutics, 2002)
Sildenafil is a phosphodiesterase-type-5 inhibitor indicated for the treatment of erectile dysfunction in men. We report a case of NAION identified from a cohort of 8,893 patients (from a Prescription-Event Monitoring study) prescribed sildenafil by their primary care physician in England between April and June 1999. This 61-year-old patient had risk factors for NAION independent of drug therapy. It was not possible to be confident about a causal association between sildenafil and NAION, though the possibility could not be ruled out. Epidemiological data suggest that one case of NAION might be expected in a cohort of 8,893 subjects. Thus it remains important for clinicians to consider the range of risk factors for NAION; while equally, the processes of pharmacovigilance need to continue as for any recently launched drug preparation.